Lange's 1938 model: dynamics and the "Optimum propensity to consume" - Michael Assous; Roberto Lampa (Duke University, Center for the History of Political Economy (CHOPE), 2014)
Oskar Lange's 1938 article "The Rate of Interest and the Optimum Propensity to Consume", is usually associated with the original IS-LM approach of the late 1930s. However, Lange's article was not only an attempt to illuminate Keynes's main innovations but the first part of a wide project that included the development of a theory of economic evolution. This paper aims at showing that Lange's article can help illuminating critical aspects of this project: in particular, Lange's idea that a synthesis between Kaldor's and Kalecki's theories and that of Schumpeter, might have been possible and that it represented (in intentions) a "modern" and consistent reconstruction of the Marxist theory of the business cycle. Section 1 clarifies Lange's early reflection on dynamics. Section 2 centers on Lange's 1938 static model and indicates the effects of a change of saving on investment. Section 3 suggests a dynamic reconstruction from which are addressed important arguments raised by Lange in a series of papers written between 1934 and 1942.
Keywords: 330; Lange; Kalecki; Marxian theory of the business cycle; marginal propensity to save; non-linearity